The Seeds Without Borders Agreement in South Asia is easing rice varieties sharing among countries - CGIAR Research Program on Rice (2020)
The Seeds Without Borders (SWB) Agreement facilitates sharing rice varieties across member countries. Through SWB Agreement, member countries can get access to improved varieties of rice, which help to increase productivity, food security and farm income and thereby achieving SDG 1 and 2.